The effect of teacher leadership on students’ purposeful learning - Verónica Fernández Espinosa; Jorge López González (Cogent Social Sciences)
Teaching leadership is a key factor for students’ learning and flourishing, and it occurs in an asymmetrical and interpersonal relationship. This research seeks to characterize the teaching leadership of high school teachers through the influence they exert on their students. It is not based on the teacher’s self-perception but on the experience that the students have had. For this purpose, a qualitative study was carried out in Spain with 200 first-year university students in which they answered four questions about the teacher who most influenced them during their high school. The results point to five leadership traits or styles that are not mutually exclusive: empathetic leadership, comforting leadership, motivating leadership, exemplary leadership, and wise leadership. In addition, moments of weakness and vulnerability in students are those that most favour the influence of the teacher in their lives, encouraging vital learning in them. This study highlights the importance of teacher leadership for student character education.